Cell death induced by taxanes in breast cancer cells: cytochrome C is released in resistant but not in sensitive cells - Ehrlichová, Marie; Koc, Michal; Truksa, Jaroslav; Naldová, Zuzana; Václavíková, Radka; Kovárr, Jan (Anticancer research, 2005)
BACKGROUND: The aim of the study was to contribute to our understanding of the mechanisms responsible for the resistance of breast cancer cells to taxanes. MATERIALS AND METHODS: Cell cycle characteristics, DNA fragmentation, p53 and p21(WAF1/CIP1) expression, caspase-3 and caspase-9 activity, cytochrome c release from mitochondria during cell death induction by the taxanes paclitaxel and docetaxel in highly-sensitive MDA-MB-435 and highly-resistant NCI-ADR-RES human breast cancer cells were compared. RESULTS: Approximately 300-fold higher concentrations of the taxanes were required to induce death in resistant NCI-ADR-RES cells than in sensitive MDA-MB-435 cells. Cell death induced by the taxanes in both sensitive and resistant cells was preceded by the accumulation of cells in the G2/M-phase. Neither cell type produced any DNA fragmentation (DNA ladder) typical of regular apoptosis. The p53 and the p21(WAF1/CIP1) levels did not change in sensitive or in resistant cells during cell death induction by the taxanes. The activity of the executioner caspase-3 increased significantly (2 to 2.5-fold) and, similarly, the activity of caspase-9 increased significantly (2 to 3.5-fold) in both cell types. However, cytochrome c was found to be released from mitochondria into the cytosol only in the resistant NCI-ADR-RES cells, but not in the sensitive MDA-MB-435 cells. CONCLUSION: The death induced by the taxanes in the studied breast cancer cells can be characterized as an apoptosis-like death, including caspase-3 and caspase-9 activation but not oligonucleosomal DNA fragmentation. However, the mechanisms of death induction by the taxanes in sensitive MDA-MB-435 cells and resistant NCI-ADR-RES cells differ. Cytochrome c is released from the mitochondria in resistant but not in sensitive cells.
Keywords: Cell Growth Processes; docetaxel; Caspase 3; Antineoplastic Agents, Phytogenic; kaspasa 3; Cell Line, Tumor; cytochromy c; fragmentace DNA; Taxoids; kaspasa 9; chemorezistence; Cell Death; buněčná smrt; nádory prsu; paclitaxel; nádorový supresorový protein p53; Paclitaxel; Caspases; inhibitor p21 cyklin-dependentní kinasy; kaspasy; DNA Fragmentation; lidé; Caspase 9; taxoidy; Breast Neoplasms; Humans; Cytochromes c; Drug Resistance, Neoplasm; nádorové buněčné linie; Cyclin-Dependent Kinase Inhibitor p21; fytogenní protinádorové látky; buňky - růstové procesy; Docetaxel; Tumor Suppressor Protein p53